Childhood abuse and neglect in intimately pierced individuals. Issue 3 (3rd July 2018) - Möller, Johanna; Peregrinova, Ludmila; Badde, Stephanie; Oddo, Silvia; Unterhorst, Katja; Stirn, Aglaja
ABSTRACT: Body piercing of the genitalia and nipples, called intimate piercing (IP), is an increasingly popular practice. However, research on psychological effects of IP is still scarce. In the present study we assessed the assumption that IP may play a key role in coping with childhood abuse, psychological distress, and body image derogations. An IP sample consisting of 71 female and male participants with at least one genital and/or one nipple piercing was assessed with psychometric tests. Indeed, the IP sample included significantly more subjects with emotional, sexual, and physical childhood abuse as well as emotional and physical neglect experiences, than expected in the German general population. On the contrary, the IP sample did not yield psychological distress symptoms of clinical relevance and showed an average body image profile. The results are discussed in light of trauma-coping strategies.